ANALYSIS OF SHARIA COMMERCIAL BANK PERFORMANCE BASED ON THE ISLAMICITY PERFORMANCE INDEX METHOD - Sri Wahyu Handayani (UG Journal, 2022)
This study aims to find out and analyze BRI Syariah's performance based on the Islam city Performance Index (IPI) method for the period 2016 to 2018. The method used is a ratio calculation, namely profit-sharing ratio (PSR), zakat performance ratio (ZPR), equitable distribution ratio (EDR), Islamic investment vs. non-Islamic investment ratio, and Islamic income vs non-Islamic income ratio. In this study, the analytical technique used is a quantitative analysis and the data used are annual financial reports for the 2016-2018 period. The results showed that the performance of Bank Rakyat Indonesia Syariah (BRIS) or BRI Syariah based on the Islam city Performance Index (IPI) method, namely in carrying out the performance of Islamic commercial banks was very good and following Islamic Sharia principles and the condition of Islamic banking was in good health.